2006
DOI: 10.1007/s00464-006-3027-3
|View full text |Cite
|
Sign up to set email alerts
|

Totally extraperitoneal (TEP) hernia repair after radical prostatectomy or previous lower abdominal surgery

Abstract: Laparoscopic TEP for inguinal hernia repair in patients after previous low abdominal surgery has good results, similar to those in patients without previous surgery. Despite a longer operative time, TEP repairs can be performed efficiently and safely in patients after prostatectomy by skilled and experienced laparoscopic surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 17 publications
0
43
1
1
Order By: Relevance
“…The recurrence rate was 0.35%. In last few years we have begun using this method for inguinal hernia diagnosed in patients who underwent previous pelvic surgery and radical prostatectomy [20].…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate was 0.35%. In last few years we have begun using this method for inguinal hernia diagnosed in patients who underwent previous pelvic surgery and radical prostatectomy [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is quite remarkable that a multiplicity of studies from urologists exists analysing the effect of previous laparoscopic hernia repair with mesh in prostate surgery while so far only one study [28] has analysed the effect explicitly from a surgical point of view, doing endoscopic inguinal hernia repair (TEP) after prostatectomy. However, in that study only 26 patients were observed, and only 10 with previous radical prostatectomy, whereas in two of these patients conversion to TAPP had to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to enter the preperitoneal space after previous surgery and to perform dissection during a TEP hernia repair due to adhesion. There have been few studies on the feasibility of TEP hernia repair after PLAS [2][3][4][5][6]. Furthermore, there have been no reports on the feasibility and safety of SILS-TEP in patients with PLAS [7,8].…”
Section: Introductionmentioning
confidence: 99%